PENGARUH AUDIT OPERASIONAL DALAM MENINGKATKAN EFISIENSI DAN EFEKTIFITAS TERHADAP KINERJA PEMBELIAN PADA PT ENVIROLAB NUSANTARA - Budi Tri Rahardjo, Ak., M.Ak., CA; Irta Paramita (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2016)
Abstract : This research was conducted in order to determine and analyze the influence of operational audit the efficiency of the performance of the purchase of PT Envirolab Nusantara, investigate and analyze the influence of operational audit the effectiveness of the performance of the purchase, determine and analyze the effect of operational audits of efficiency and operational audits effectiveness jointly on the performance of purchase PT Envirolab Nusantara. Based on the test results "t" obtained the value t = 2.683> t table = 2.052 then Ho is rejected and Ha accepted, which means there is significant influence between the variables X1 (operational audit efficiency) to variable Y (purchase performance) with a regression coefficient of 0.334. Based on the test results "t" obtained the value t = 3,376> t table = 2.052 then Ho is rejected and Ha accepted, which means there is significant influence between the variables X2 (operational audit effectiveness) to variable Y (purchase performance) with a regression coefficient of 0.408. From the results of the overall study are based on F test that showed Fhitung = 37.844> F table = 3.354 then Ho is rejected and Ha is received it can be concluded that each variable operational audit efficiency, and operational audits effectiveness jointly have a significant effect on performance purchase. Based on the results of multiple regression test found the coefficient of determination (R Square) of 0.737. This means that the independent variable (operational audit operational audit efficiency and effectiveness) contribute to dependent variable (performance purchase) of 73.7% while the remaining 26.3% is influenced by other factors not examined.